Seasonality effects on the movement pattern of the Pantanal Sul-Mato-Grossense Jaguar (Panthera onca) - Monarcha, Julia Mortatti; Kanda, Claudia Zukeran (Revista Hipótese, 2019)
The Pantanal of Mato Grosso do Sul flood dynamics has been affected by human activities that are changing the species movement patterns. The aim of this study is to understand how seasonality interferes with the jaguar movement, by GPS monitoring. The metodology consists in the likelihood approach and selection of competitive models. Jaguar females showed a Lévy walk and jaguar males showed an exponential walk, contributing to support locals conservation politics.
Keywords: Movement Ecology; Felidae; Landscape Ecology; Conservation